Sex steroid profiles, gonadal histology and early development of clarias batrachus linneaus in captivity - Argungu, Lawali Alkali (2014)
Clarias batrachus is a local species in South East Asia and is the most popular in terms of aquaculture and aquarium trade among Asian species. Its excellent nutritional profile and ability to perform in water environments with depleted water quality condition has made it a good candidate for aquaculture. It could accommodate high density stocking and ensure high yield per unit area. The fish is threatened and is getting extinct due to overexploitation of water resource, habitat loss, and unguarded introduction of exotic species such as Clarias gariepinus and indiscriminate use of agrochemicals particularly pesticides in the paddy fields which is the popular natural breeding ground of the species. This has made it increasingly difficult to obtain the seed of the species from the wild. Aquaculture is the only platform upon which the extinction of this promising species can be arrested and the fact that hatchery-bred fish has to be induced to spawn due to lack of spontaneous spawning in captivity has made the study of the reproductive biology of this species a necessity. Consequently, reproductive hormonal profile and gonadal development of C. batrachus were investigated at the University Putra Malaysia Aquaculture Research Station in Puchong, Selangor, Malaysia from February 2012 to January 2013. The brood stocks for the study were obtained from the wild at Negeri Sembilan. Commercial Enzyme Linked Immunosorbent Assay (ELISA) was used to assay plasma sex steroid hormones, 17β-estradiol, 11-ketotestosterone and testosterone. The range values of 17β-estradiol, 11-ketotestosterone, male and female testosterones were 111.68 ± 3.62 pg/ml (December) to 695.30 ± 8.94 pg/ml (October), 6.61 ± 0.24 pg/ml (September) to 80.27 ± 5.29 pg/ml (August), 26.67 ± 0.98 pg/ml (September) to 209 21 ± 19.49 pg/ml (October) and 7.02 ± 0.06 pg/ml (February) to 49.99 ± 2.17 pg/ml (October) respectively. The monthly values of 17β-estradiol, 11-ketotestosterone and testosterone were significantly different (P<0.05) and the profiles of the steroid hormones have exhibited several peak levels during the study period implying the ability of the fish to spawn several times in a year. At the same time several stages of oocyte development were always found in the ovary while evidence of continuous spermatogenesis was detected in the testes proving that C. batrachus is a non-seasonal breeder. Induced breeding using different doses (0.7, 1.0, 1.3, 1.6 and 1.9 ml/kg BW of fish) of synthetic hormone, ovaprim was investigated. Fecundity, ovulation rate, fertilization rate, hatching rate and survival rate were the parameters used to judge the performance of the various doses and 1.0 ml of ovaprim per kg body weight of female fish was found to guarantee the best performance in the induced breeding of C. batrachus. The shortest latency period (12hours) on record was recorded in this study on all tested doses of ovaprim. The impact of ovaprim on the plasma sex steroid levels were investigated at different doses and time-intervals (0.7, 1.0, 1.3, 1.6 and 1.9 ml/kg BW at 0, 6, 12, 18 and 24 hours) and saline solution was used as control. The result revealed that, ovaprim was effective in elevating plasma sex steroid levels. Embryonic and larval development of the fish was also evaluated. The developmental events were found to be in conformity with what was reported by several scholars on catfish. However, hatching was observed to be accomplished within 24-30 hours post fertilization. Some individuals were noticed to have absorbed their yolk-sac on the third day but majority fully utilized the yolk-sac on the fourth day. This characteristic has implication on the survival and management of the larva of this species if early mortality and cannibalistic tendencies are to be controlled. The outcome of the study has shown that C. batrachus is a non-seasonal breeder which can breed several time in a year.